Participatory investigation of Contagious Caprine Pleuropneumonia (CCPP) in goats in the Hammer and Benna-Tsemay districts of southern Ethiopia - Mekuria, S.; Zerihun, A.; Gebre-Egziabher, B.; Tibbo, Markos (Springer, 2008)
The study was conducted in two selected districts of Southern Omo zones of Ethiopia, namely Hammer and Benna-Tsemay, during November 2004 and May 2005 to determine the status of contagious caprine pleuropneumonia (CCPP). Participatory disease investigation was conducted in the goat flocks owned by pastoralists of the districts. Participatory methods such as proportionate piling and matrix scoring of diseases were used to characterise major diseases of goats. Clinical and post-mortem examinations and isolation of the causative agent of CCPP were done. Serological tests were conducted using CFT. CCPP (locally termed Sompo) ranked as the first important disease of goats in the study area. Local perception of causes and signs of CCPP were described. Matrix scoring between groups revealed that disease signs and causes showed weak, moderate and good agreement by Kendall's coefficient concordance (W = 0.21-0.99). The overall sero-prevalence of CCPP was 15.5%. The causative agent was isolated from sick animals in the lab. The characteristic clinical signs, gross lesions, bacteriological isolation of the causative agent supported by participatory epidemiological disease investigation revealed that CCPP is a major disease of goats in the study districts. Participatory epidemiology using indigenous knowledge could efficiently be used to generate sufficient information with minimum cost, local materials and within reasonably short period of time, assisting the designing of feasible disease control programme in developing countries.